How can HR drive growth? (Cheltenham Edward Elgar Publishing Ltd, 2013)
The ten up-to date research reviews that are presented in this book provide new insights into the HR academic literature. The chapters provide clear lessons that can be learnt from, along with strategies, approaches and processes in which HR could be used by both practitioners and policy makers to drive growth.
Includes index
Keywords: Human Resource